Optical Electronics : An Introduction - Yan, Jixiang (De Gruyter Textbook, 2019)
This book discusses light transmission and extends to more applied fields of laser and laser technology, photoelectric detection and devices, photoelectric imaging and systems with explainations on theories and engineering applications. Addressing the intersection between optics and electrical engineering, the textbook prepares graduate students to photoelectronics and can also be used as reference for engineers.